Methods of decision of professional situations of the future specialists of physical education. - Pechko O.M. (Pedagogìka, Psihologìâ ta Mediko-bìologìčnì Problemi Fìzičnogo Vihovannâ ì Sportu, 2011)
The features of choice of methods of decision of professional situations students are considered. 30 students took part in an experiment. Information of the questionnaire questioning is utilized. Pedagogical situations which arise up on employments on a physical culture at middle school are considered. It is set that participating in the decision of concrete pedagogical situations develops for students skills of self-examination, self-control and self-appraisal. It is set that tactic of conduct of students in the conditions of decision of concrete professional situation is conditioned the level of professional thought. The methods of decision of professional situations which must be directed on the search of general looks and actions are recommended.